New species and phylogeny of landhoppers in the genus Waematau Duncan, 1994 (Crustacea: Amphipoda: Talitridae) from northern New Zealand - Ball, Olivier J.-P.; Webber, W. Richard; Shepherd, Lara D. (Zootaxa, 2017)
The talitrid landhopper genus Waematau Duncan, 1994 is restricted to the northern North Island of New Zealand. Six species of Waematau from Te Paki Ecological District are documented. Three known species, Waematau muriwhenua Duncan, 1994, W. reinga Duncan, 1994 and W. unuwhao Duncan, 1994, are redescribed and three new species, W. kohuroa sp. nov., W. rereke sp. nov. and W. ringanohinohi sp. nov. are described, bringing the total number of known Waematau species to eight. A molecular phylogenetic analysis of all eight known Waematau species was conducted using DNA sequences from the CO1, 16S and histone H3 loci. Results show a high degree of congruence between the molecular phylogeny and morphological characters distinguishing the species. Molecular analysis also supports recognition of the three new species, despite low levels of interspecific morphological variation for certain traits. We identify the most obvious morphological indicators of evolutionary change between closely related species of Waematau, and predict that the New Zealand landhopper fauna is richer than currently recognised.